Social policy of France in the context of inter-ethnicharmony (Journal of Philosophy Culture and Political Science, 2018)
In this article researching development and formation of French social policy and its relation to the modern diasporas and ethnic minorities which habits in the territory of this state, also researchers analyze the features of providing social guarantees and provisions to the ethnic minorities and to the first generation migrants. Researchers made a try, to identify the features of French social system and dialogue between power representatives with different cultures unions with the purpose of creation special institutes and competent authorities which dedicated to provide a social welfare to the ethnic minorities and diasporas in the modern France.Key words: Social policy, social welfare. Ethnicminorities, Diasporas, immigrants.